The effect of Health, Safety and Environment Management System (HSE-MS) on the improvement of safety performance indices in Urea and Ammonia Kermanshah Petrochemical Company - M. S. Poursoleiman (بهداشت و ایمنی کار, 2015)
Introduction: Work-related accidents may cause damage to people, environment and lead to waste of time and money. Health, Safety and Environment Management System has been developed in order to reduce accidents. This study aimed to investigate the effect of implementation of this system on reduction of the accidents and its consequences and also on the safety performance indices in Kermanshah Petrochemical Company. .Material and Method: In this study, records of accidents were collected by OSHA incident report form 301 over 4 years. Following, the mean annual accidents and its consequences and safety performance indices were calculated and reported. Then, using statistical analysis, the impacts of two years implementation of this system on the accidents and its consequences and safety performance indices were evaluated. . Result: The results showed that the implementation of HSE system was significantly correlated with Frequency Severity Indicator, Accident Severity Rate, lost days, minor accidents and total incidents (P-value 0.05). .Conclusion: The implementation of Health, Safety and the Environment Management System caused a reduction in accidents and its consequences and most of the safety performance indices in the entire process cycle of Kermanshah Petrochemical Company. Overall, safety condition has been improved considerably.